PENGARUH SUHU DAN LAMA FERMENTASI TERHADAP UJI ORGANOLEPTIK PADA PEMBUATAN NATA BUAH ENAU (Areng pinnata Merr) - Marselia Latumahina; Ali Awan; Dominggus Rumahlatu (Program Studi Pendidikan Biologi FKIP Unpatti, 2017)
Background: Enau is one of the natural resources in the tropics, its distribution is widespread, very necessary and easy to obtain for daily use by local people as a sustainable natural resource. Palm fruit in terms of chemical composition has a low nutritional value, but